(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2025)
Bharati Mukherjee’s novels make important contributions to the field of diasporic literature because they deal with the themes of expatriation and immigration, as well as feminism and transformation. Her works depict the emotional, psychological, and cultural conflicts of immigrants striving to make sense of their traditional values and customs when forced to navigate the challenges of Western culture. This paper aims at examining selected novels like The Tiger’s Daughter, Wife and Jasmine so as to analyses the experiences of displacement, alienation, identity crisis and self-transformation suffered by female protagonists. The study also examines the process of immigration as psychological and cultural reconstruction as depicted by Mukherjee. Her female protagonists defy male limitations, fight racial and cultural prejudice and slowly construct their subjectivities in transnational locales. Mukherjee conveys the complications of being bicultural and the search for hybrid identities through a series of feminist portraits of immigrant women caught between tradition and modernity. The paper also explores how the protagonists’ journeys towards selfhood and independence are influenced by feminism. In conclusion, this study has confirmed that transformation is the main motive in Mukherjee’s fiction, a process through which her characters can overcome oppression and reconstruct themselves in the multicultural societies.